'Timescapes' in doctoral education: the politics of temporal equity in higher education. Issue 6 (19th September 2019) - Manathunga, Catherine
ABSTRACT: In the twenty-first century, the politics of higher education in Australia and around the globe have become dominated by neoliberal agendas of efficiency, profitability and managerialism. This has fundamentally altered the 'timescapes' of higher education. In the case of doctoral education, doctoral candidates and supervisors are subjected to increasing time pressures and required to produce a wide variety of outcomes in very short timeframes. These managerial agendas of efficiency and speed impact upon all doctoral candidates and supervisors but present particular practical and epistemic difficulties for Indigenous, migrant, refugee and international students. In this article, I illustrate how fast doctoral timescapes encourage assimilationist pedagogies that have been shown to be especially detrimental for Indigenous, migrant, refugee and international doctoral candidates. Drawing upon a complex array of theoretical resources that investigate Lefebvre's rhythm analysis and other authors' notions of epistemic time and the ethics of time, this article argues for a reconceptualization of doctoral timescapes in order to promote a politics of temporal equity in doctoral education. This especially involves making space for epistemic, lived and eternal temporal rhythms in doctoral education policy and practice.